Golgi/plastid‐type manganese superoxide dismutase involved in heat‐stress tolerance during grain filling of rice. Issue 9 (14th January 2015) - Shiraya, Takeshi; Mori, Taiki; Maruyama, Tatsuya; Sasaki, Maiko; Takamatsu, Takeshi; Oikawa, Kazusato; Itoh, Kimiko; Kaneko, Kentaro; Ichikawa, Hiroaki; Mitsui, Toshiaki
Summary: Superoxide dismutase (SOD) is widely assumed to play a role in the detoxification of reactive oxygen species caused by environmental stresses. We found a characteristic expression of manganese SOD 1 ( MSD1 ) in a heat‐stress‐tolerant cultivar of rice ( Oryza sativa ). The deduced amino acid sequence contains a signal sequence and an N ‐glycosylation site. Confocal imaging analysis of rice and onion cells transiently expressing MSD1‐YFP showed MSD1‐YFP in the Golgi apparatus and plastids, indicating that MSD1 is a unique Golgi/plastid‐type SOD. To evaluate the involvement of MSD1 in heat‐stress tolerance, we generated transgenic rice plants with either constitutive high expression or suppression of MSD1 . The grain quality of rice with constitutive high expression of MSD1 grown at 33/28 °C, 12/12 h, was significantly better than that of the wild type. In contrast, MSD1 ‐knock‐down rice was markedly susceptible to heat stress. Quantitative shotgun proteomic analysis indicated that the overexpression of MSD1 up‐regulated reactive oxygen scavenging, chaperone and quality control systems in rice grains under heat stress. We propose that the Golgi/plastid MSD1 plays an important role in adaptation to heat stress.